O ensino religioso não confessional no currículo da escola pública da Paraíba segundo gestores e especialistas - Holmes, Maria José Torres (2024)
This Thesis is titled Non-Confessional Religious Education in the Curriculum of Public Schools in Paraíba, according to Education Managers and Specialists. Its interface with the National Permanent Forum of Religious Education (FONAPER) and its dialogue with religious and Cultural Diversity favors the interpretation of Religious knowledge as the object of study of this curricular subject by valuing the Religious phenomenon of Religious Cultural Traditions. The main objective is to analyze the comprehension of educational managers, pedagogical coordinators, and specialists from public schools in the Educational System of Paraíba about the importance of non-confessional Religious Education in the curriculum of state and municipal schools. The object of this study is the development of this subject in eight (8) Public Schools in Paraíba. Therefore, the methodological framework and theoretical basis of bibliographical research include authors such as Barcellos and Farias, Campos, Eliade, Figueiredo, Freire, Otto, Oliveira et all, among others. Just like Moscovici with Social Representation, fundamental for field research. It is necessary to mention works on current Legislation, Brazilian Constitutions from 1824 to 1988, and Educational Laws (LDB). The first: 4020/1961; the second: 5672/1971; the third: 9394/1996, in addition to the Common National Curriculum Base (BNCC) in its three versions: 2015, 2016, and 2017, as well as the Curricular Proposal of Paraíba (PCPB). The approach is qualitative-quantitative-comparative, starting with a detailed bibliographical survey and moving on to an exploratory and descriptive case study, carried out in four(4) municipal and four (4) state schools. The research tools used were observation, a field diary, a questionnaire and a semi-structured participant interview. The results reveal interesting data to contribute to the Initial and Continuing Education of Religious Education Teachers, as well as providing consistent data that favors the construction of a strategic plan for the provision of public policies for this curricular component in the Brazilian Public and/or Private Education Systems.